2014
DOI: 10.1039/c4ta05613b
|View full text |Cite
|
Sign up to set email alerts
|

High voltage in hole conductor free organo metal halide perovskite solar cells

Abstract: High voltage hole conductor free perovskite solar cell achieved 1.35 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 23 publications
3
59
1
Order By: Relevance
“…Both patterns are of ring-type, which indicates the presence of a large number of randomly-oriented nanoscale crystallites in each of the perovskite layers. The strongest diffraction is observed around inter-planar spacing of 3.17-3.2 Å in both patterns, which reasonably matches the reported data for the tetragonal I4/mcm (a = b = 8.87 Å, c = 12.67 Å) perovskite [25,28,31]. However, the sets of diffraction reflexes appearing in both patterns do not coincide.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Both patterns are of ring-type, which indicates the presence of a large number of randomly-oriented nanoscale crystallites in each of the perovskite layers. The strongest diffraction is observed around inter-planar spacing of 3.17-3.2 Å in both patterns, which reasonably matches the reported data for the tetragonal I4/mcm (a = b = 8.87 Å, c = 12.67 Å) perovskite [25,28,31]. However, the sets of diffraction reflexes appearing in both patterns do not coincide.…”
supporting
confidence: 78%
“…Cross-section TEM images of the devices are presented in Figure 1A,B. The thicknesses of metal oxides-which demonstrate high PCEs that we studied in this work-are based on our previous reports [15,28]. The current voltage curves of this study's cells are shown in Figure 2A, the hole conductor free TiO 2 / MAPbI 3 cell has V oc of 0.85 V, current density (Jsc) of 18 mA/cm 2 , fill factor (FF) of 56% with efficiency of 8.5%.…”
Section: Resultsmentioning
confidence: 99%
“…This device performance surpasses, by over 17%, other hole-transporting layer (HTL)-free polycrystalline MAPbBr 3 solar cells reported to date, [29,30] and is even comparable to those of devices with a HTL. [25,31] The average efficiency of 12 monocrystalline devices using this structure with 1 to 4 µm thick crystals is 5.67 ± 0.44% ( Figure S9, Supporting Information).…”
mentioning
confidence: 65%
“…This is in agreement with the energy difference between the Fermi levels of TiO 2 and MAPbBr 3 (ΔE~1.4 eV), which is larger than that between ITO and MAPbBr 3 . The V OC is also the highest among reported MAPbBr 3 solar cells without a HTL, [29,30] and is on par with the best performing cells with a custom-designed HTL. [25] Such improvements clearly imply that the TiO 2 /perovskite-based devices extract electrons more efficiently than ITO/perovskite based devices.…”
mentioning
confidence: 83%
“…The p-type nature of the Br perovskite has been suggested in the past both in experimental and theoretical papers 36,37 . Our EBIC results support this finding and illustrate for the first time the working mechanism of this photovoltaic device.…”
Section: Main Textmentioning
confidence: 99%